STUDI KOMPARASI TERHADAP TINDAK PIDANA PERZINAAN (DUSA) MENURUT HUKUM ADAT DAYAK SEBERUANG DI KECAMATAN TEMPUNAK DAN HUKUM POSITIF INDONESIA - PANKRASIUS YORRIS GIO NIM. A1012191044 (Jurnal Fatwa Hukum, 2023)
Abstrac The Dayak Seberuang community recognizes the existence of the Dusa Adat, Dusa itself is adultery or sexual relations outside of marriage. The act of Dusa in the Dayak Seberuang community is an act that is considered to have very fatal consequences because it is believed that if an act of dusa occurs, if left unchecked, it will cause havoc for the offender and the area where the act occurred.In positive law (KUHP) article 284, adultery is defined as an extramarital relationship between a man who is not married and a woman who is married, or vice versa, a relationship between a woman who is not married and a man who is married. In this writing the author uses a normative juridical method which is carried out by researching literature and also called library law research to obtain theoretical data related to this problem and associated with the provisions of customary law norms of the Dayak Seberuang community in Tempunak District, and using a comparative approach ( comparative approach) between customary law and Indonesian positive law in the crime of adultery. And the data collection technique used is by means of interviews and literature studies, then the data that has been obtained is processed and analyzed and then presented descriptively. In customary law and positive law, adultery (Dusa) is defined as sexual relations outside of marriage, but what distinguishes it is that in Article 284 of the Criminal Code, adultery is defined as sexual relations outside of marriage between a man who is not married and a woman who is married, or vice versa. between an unmarried woman and a married man. In Law No. 1 of 2023 concerning the Criminal Code, article 411 of adultery is defined as anyone who has intercourse with someone who is not his husband or wife, is convicted of adultery. In the Seberuang Dayak community, the perpetrators of the crime of adultery or adultery are required to pay customary fines in the form of items considered to have magical value that can restore the magical balance that was disrupted as a result of the violation of these customs. In Article 284 of the Criminal Code for the perpetrators of the crime of adultery, it is punishable by imprisonment for a maximum of nine months and in UURI No. 1 of 2023 concerning the Criminal Code, article 411 for the perpetrators of the crime of adultery, the perpetrators of the crime of adultery are sentenced to imprisonment for a maximum of 1 (one) year or a fine. mostly category II.Keywords: Dusa, adultery, comparison of law Abstrak Masyarakat Dayak Seberuang mengenal adanya Adat Dusa, Dusa itu sendiri ialah perzinahan atau hubungan seksual diluar nikah. Perbuatan Dusa pada masyarakat Dayak Seberuang merupakan suatu perbuatan yang dianggap sangat fatal akibatnya karena diyakini apabila terjadi suatu perbuatan dusa bila dibiarkan begitu saja maka akan menimbulkan suatu malapetaka bagi pelaku pelanggaran dan daerah tempat dimana perbuatan itu terjadi.Dalam hukum positif (KUHP) pasal 284 zina diartikan sebagai hubungan diluar nikah antara seorang laki-laki yang belum beristri dengan perempuan yang telah bersuami, atau sebaliknya hubungan antara seorang perempuan yang belum bersuami dengan laki-laki yang sudah beristri. Dalam penulisan ini penulis menggunakan metode secara yuridis normatif yang dilakukan dengan cara meneliti bahan pustaka dan disebut juga penelitian hukum kepustakaan untuk mendapatkan data teoritis yang berhubungan dengan masalah ini dan dikaitkan dengan ketentuan norma hukum adat masyarakat dayak seberuang di Kecamatan Tempunak, dan menggunakan pendekatan perbandingan (comparative approach) antara hukum adat dan hukum positif Indonesia dalam tindak pidana perzinahan. Dan teknik pengumpulan data yang digunakan adalah dengan cara wawancara dan studi kepustakaan, kemudian data yang telah diperoleh diolah dan dianalisis kemudian disajikan secara deskriptif. Dalam hukum adat dan hukum positif zina (Dusa) sama diartikan sebagai hubungan seksual diluar nikah, namun yang membedakannya adalah dalam pasal 284 KUHP zina diartikan sebagai hubungan seksual diluar nikah antara seorang laki-laki yang belum beristri dengan perempuan yang telah bersuami, atau sebaliknya hubungan antara seorang perempuan yang belum bersuami dengan laki-laki yang sudah beristri. Dalam Undang-Undang No 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana, pasal 411 perzinaan diartikan sebagai setiap orang yang melakukan persetubuhan dengan orang yang bukan suami atau istrinya, dipidana karena perzinaan. Dalam masyarakat dayak seberuang para pelaku tindak pidana perzinaan atau dusa diharuskan untuk membayar denda adat berupa barang-barang yang dianggap mempunyai nilai magis yang bisa mengembalikan keseimbangan magis yang sempat terganggu akibat dari terjadinya pelanggaran adat tersebut. Didalam pasal 284 KUHP bagi pelaku tindak pidana perzinaan diancam pidana kurungan penjara paling lama sembilan bulan dan dalam UURI No 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana pasal 411 bagi pelaku tindak pidana perzinaan dipidana penjara paling lama 1 (satu) tahun atau pidana denda paling banyak kategori II.Kata kunci : Dusa, zina, perbandingan hukum